2005
DOI: 10.1113/jphysiol.2005.085506
|View full text |Cite
|
Sign up to set email alerts
|

Null mutation of myeloperoxidase in mice prevents mechanical activation of neutrophil lysis of muscle cell membranes in vitro and in vivo

Abstract: Membrane lysis is a common and early defect in muscles experiencing acute injuries or inflammation. Although increased mechanical loading of muscles can induce inflammation and membrane lysis, whether mechanical loads applied to muscle can promote the activation and cytolytic capacity of inflammatory cells and thereby increase muscle damage is unknown. We tested whether mechanical loads applied to mouse muscle cells in vitro can increase membrane lysis, and whether neutrophil-mediated lysis of muscle cells is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 45 publications
(61 reference statements)
0
54
0
3
Order By: Relevance
“…Their action on the necrotic tissue relies on proteolysis, oxidation and phagocytosis. Muscle-specific inhibition of neutrophil/monocyte activation results in a delay in regeneration upon acute injury (Nguyen et al, 2005).…”
Section: Cellular Regulators Of Muscle Repair and Their Regenerative mentioning
confidence: 99%
“…Their action on the necrotic tissue relies on proteolysis, oxidation and phagocytosis. Muscle-specific inhibition of neutrophil/monocyte activation results in a delay in regeneration upon acute injury (Nguyen et al, 2005).…”
Section: Cellular Regulators Of Muscle Repair and Their Regenerative mentioning
confidence: 99%
“…CD206 is a mannose receptor that binds and internalizes sugar moieties on molecules present at high levels in inflamed tissue. In the context of muscle damage and regeneration, MPO is an important ligand for CD206 (101) because it serves a prominent role in muscle membrane lysis that is caused by neutrophils (79), and its ligation and internalization by M2 macrophages would reduce cytotoxicity. CD206 expression by M2 macrophages is promoted by anti-inflammatory cytokines, and its binding increases the expression of anti-inflammatory cytokines, leading to positive feedback that can enable M2 macrophages to more rapidly deactivate Th1 cells that are capable of free radical-mediated damage of muscle cells.…”
Section: M1 Macrophages Express Cd68mentioning
confidence: 99%
“…Loading alone caused only a 1.7% lysis of muscle cells, while coculturing with neutrophils in the absence of loading resulted in only 3.5% lysis. However, loading in the presence of neutrophils resulted in 12.6% lysis of muscle cells under otherwise identical culture conditions in the presence of SOD (Nguyen et al, 2005). These observations provide a direct link between changes in mechanical loads applied to tissue, and an increase in damage that is induced by inflammatory cells.…”
Section: Oxidative Metabolism Of Neutrophilsmentioning
confidence: 57%
“…Similarly, administration of catalase decreases hydrogen peroxide concentration and reduces tissue damage during reperfusion (Smith et al, 1989). In the investigation of Nguyen (Nguyen et al, 2005) it was concluded that neutrophils play a significant role in injuring cell membranes reloading following periods of unloading, and that this membrane damage was mediated by MPO. A substantial, synergistic effect on the level of muscle lysis when both mechanical loading and neutrophils were applied to muscle cells in vitro was found.…”
Section: Oxidative Metabolism Of Neutrophilsmentioning
confidence: 99%